2021
DOI: 10.1186/s12884-021-04168-8
|View full text |Cite
|
Sign up to set email alerts
|

Universal versus selective screening for gestational diabetes mellitus among antenatal clinic attendees in Abakaliki: using the one-step 75 gram oral glucose tolerance test

Abstract: Aim To compare universal screening with selective risk factor based screening for GDM, using the one-step 75 g oral glucose tolerance test (OGTT). Materials and method A cross-sectional, comparison between universal and selective risk factor based screening for GDM, among 400 antenatal care clients at Alex-Ekwueme Federal University Teaching Hospital Abakaliki (AE-FUTHA). All the participants had 75 g OGTT at 24–28 weeks of gestation and risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The results showed that the GDM incidence was higher with the universal screening (11.51%) than for the selective screening (7.93%), which provided a miss rate of 31.11%. They also found positive correlations between hyperglycemia and previous history of GDM and hypertension, weight ≥ 90 kg, and age ≥ 35 years [ 39 ].…”
Section: Africamentioning
confidence: 99%
“…The results showed that the GDM incidence was higher with the universal screening (11.51%) than for the selective screening (7.93%), which provided a miss rate of 31.11%. They also found positive correlations between hyperglycemia and previous history of GDM and hypertension, weight ≥ 90 kg, and age ≥ 35 years [ 39 ].…”
Section: Africamentioning
confidence: 99%
“…In a retrospective study comparing universal and selective screening (based on high risk using ADA criteria), 18,000 patients were examined [19]. If only high-risk patients were screened, 3% of women would remain with undiagnosed GDM.…”
Section: Methods Of Screening and Diagnosingmentioning
confidence: 99%
“…There are two main approaches to screening for GDM: universal testing, which evaluates all patients, and selective testing, which focuses on high-risk individuals. High-risk individuals include overweight or obese women with a history of giving birth to large babies, a family history of type 2 diabetes, or a personal history of gestational diabetes [4,5].…”
Section: Introductionmentioning
confidence: 99%